Students’ Critical Thinking Improvement Through PDEODE and STAD Combination in The Nutrition and Health Lecture - Tabitha Wulandari; Mohamad Amin; Siti Zubaidah; Mimien IAM (Institute of Advanced Engineering and Science, 2017)
Students’ critical thinking skills are very important in the 21st century. Learning strategies can play a role in enhancing students’ critical thinking skills in the Nutrition and Health lecture. The results of a survey in 2013 showed that the implementation of learning strategies had not given students the opportunity to practice their critical thinking skills optimally. The new strategy, a combination of PDEODE and STAD, can be used to overcome the occurring problems. The purpose of this research was to determine the increase in students’ critical thinking skills in the nutrition and health lecture after they were taught using a combination of PDEODE and STAD. This was a pre-experimental research using a one group pretest-posttest research design. The samples of this research were one class consisting of 41 university students. The results of the test were analyzed with quantitative methods, by using statistical analysis, paired samples T-test, and to know the effectiveness using gain scores. The results showed that the significance was 0.000 (p <0.05) and the gain score was 0.58. Thus, it can be concluded that the strategy of combining PDEODE and STAD can effectively improve the students’ critical thinking skills in the nutrition and health lecture.